Simulation Model of Logistic Support to Isolated Airspace Smveillance Radar Stations - Crnković, Tomislav; Bazijanac, Ernest; Basch, Danko (Promet - Traffic&Transportation, 2008)
A simulation model of the radar network operation of fivemilitary radar stations has been developed. Simulation waspeiformed in GPSS language and contains the time of operationof five radars through a period of one year, time of plannedpreventive maintenance, irregularities, time of corrective maintenanceand maintenance team(s). The simulation shows theinfluence of the number of maintenance teams on the availabilityof each radar and presents a good orienteering point fordefining the optimal model of preventive and corrective maintenanceof the radar network.